PERLUASAN AKSEPTASI DIGITAL QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) MELALUI PENGUATANSTRATEGI BAURAN PEMASARAN SAVE (SOLUTION, ACCESS, VALUE, EDUCATION) DI KALIMANTAN TIMUR - Adi Purbondaru (Bajang Institute, 2024)
The development of digital technology has driven the transformation of payment systems toward more efficient, inclusive, and secure cashless transactions. Quick Response Code Indonesian Standard (QRIS) is a digital payment standard developed by Bank Indonesia to promote financial inclusion through fast, easy, and integrated transactions. This study aims to analyze the impact of a marketing strategy based on the SAVE model (Solution, Access, Value, Education) on user satisfaction and the expansion of QRIS adoption in East Kalimantan. A quantitative approach was employed, with data collected through surveys of 80 respondents comprising individual users and business operators in three major cities: Samarinda, Balikpapan, and Berau. The results indicate that all four elements of the SAVE marketing mix significantly influence user satisfaction. The solution-based strategy (Solution) effectively addresses users' specific needs through flexible transaction options. Accessibility (Access) ensures that QRIS is available across various channels, both physical and digital, providing convenience for users to transact anytime and anywhere. The added value (Value) perceived by users, such as ease of use, speed, and security, serves as a key factor in increasing user loyalty to QRIS. Education (Education) delivered through socialization, interactive activities, and multi-directional communication successfully enhances public awareness and understanding of the benefits and security of QRIS usage. The study also found that user satisfaction has a direct impact on the expansion of QRIS adoption, as satisfied users are more likely to continue using QRIS and recommend it to others. These findings affirm the relevance of the SAVE marketing model as a more appropriate approach to addressing the challenges and dynamics of the modern market compared to the traditional 4P marketing mix. This research contributes theoretically to the literature on digital marketing strategies and financial technology adoption, while also offering practical recommendations for Bank Indonesia and stakeholders to develop more effective marketing policies and programs. Strengthened synergies among institutions are expected to further enhance QRIS adoption in East Kalimantan, support national financial inclusion, and accelerate the growth of the digital economy.